Voice made visible : multi-octave voice training and techniques for performers - Lopez-Barrantes, Rafael (Routledge, 2024)
"Voice Made Visible is an exploration of voice training and performance practice based on the use and application of Multi-Octave Vocal Range techniques. "Multi-Octave" is understood as the arsenal of sounds that exists uniquely within each human voice, beyond the comfortable average octave that we use in everyday life. In Voice Made Visible, Rafael Lopez-Barrantes builds on the voice work created by Alfred Wolfsohn and developed by Roy Hart and his company in France to assist students, artists, and those interested in the performing arts with their vocal practice. He draws from over three decades of multi-cultural performance and teaching, sharing the three fundamental pillars of his system: Fiction, News, and Body Source. This book will help readers unfold their understanding of the voice by strengthening it and inspire them to create new vocal paths for the stage, camera, and voice acting, as well as for their own personal expressive growth. Voice Made Visible is an invaluable resource for students of Acting and Voice courses, as well as working performing artists. For supplemental material, including pedagogical audio-visual clips, please visit www.barrantesvoicesystem.com"--